A new species of Scinax (Anura, Hylidae) of the S. ruber clade from Minas Gerais, Brazil - de Oliveira Drummond, Leandro; Baêta, Délio; Pires, Maria Rita Silvério (Zootaxa, 2007)
We describe a new species of treefrog from the ruber clade of the genus Scinax, from Serra do Cabral, State of Minas Gerais, Brazil. Scinax cabralensis is characterized by a small size, slightly arched and faintly distinct canthus rostralis, spotted pattern of coloration on dorsum, thighs with transversal bars, granular skin on dorsum and venter, rounded snout in dorsal view, and distinct advertisement call. Additionally, data on advertisement and territorial calls and notes on natural history and habitat are provided.